Morphofunctional characteristics of single combats athletes as factors of success - Leonid V. Podrigalo; Olha O. Podrihalo; Wladyslaw Jagiello; Olexandr V. Podavalenko; Irina P. Masliak; Yuri M. Tropin; Margarita A. Mameshina; Volodymyr О. Galimskyi; Inna І. Galimska (Physical Education of Students, 2021)
Background and Study Aim.  The aim of the article is a comparative analysis of the morphofunctional characteristics of athletes of various types of martial arts as factors of success.